The Influence of Bank XYZ Woman Based Savings Account’s Benefits on Consumer’s Decision to Open Bank XYZ’s Woman Based Savings Account - Garbiela Jesselyn; Natashia Sally (iBuss Management, 2014)
The competition in the banking industry in Indonesia is getting more intense as there are currently 10 leading banks based on assets operating in Indonesia. To survive in this industry, banks are racing to stay ahead of the competition by continuously improving the quality of their products and services. Although Bank XYZ is one of the leading banks in Indonesia, the rise of many banks in Indonesia makes it hard for Bank XYZ to sustain its position. This research aims to help Bank XYZ to face this fierce competition by identifying the benefits that significantly influence the consumer’s decision to open Bank XYZ’s woman based savings accounts. To gather the data, the researchers use simple random sampling method and distributed questionnaires to 135 Bank XYZ’s woman based savings account customers. The data is analyzed using Multiple Linear Regression Analysis. The result shows that the benefits offered in Bank XYZ’s woman based savings account simultaneously has significant influence on the consumer’s decision to open Bank XYZ’s woman based savings account and individually, insurance provision, opening gift, and design are the benefits that have the most significant influence on the consumer’s decision to open Bank XYZ’s woman based savings account. Therefore, the researchers suggest that Bank XYZ should focus on improving the benefits that matters most to the customer. Keywords: Benefits, Consumer Decision, Banks, Saving Account